THE CONCEPT OF TOURISM HUMAN RESOURCES DEVELOPMENT BASED ON REGIONAL KNOWLEDGE IN THE INTERNATIONAL BALI TOURISM INSTIUTE - I Wayan Eka Sudarmawan (Jurnal Ilmiah Hospitality Management, 2016)
ASEAN Economic Community which will be implemented by the end of 2015 brings impact on flooding of professional workforce which indicated will be invading Indonesia especially in tourism sector. Several effort had been taken by Indonesian Government to overcome this issue, one of the effort is by issuing Government Regulation Number 52 year 2012 on competency certification and business certification in tourism sector mentioning competency certification development in which all qualified workforce need to be certified. This led STPBI to certify it students with ASEAN/ACCSTP Schematic before graduation so they can compete in AEC era. To be able to use ASEAN/ACCSTP Schematic to it students, the concept of tourism human resources development and curriculum of STPBI need to be conformable with ASEAN/ACCSTP Schematic, so that when the assessment implemented, students will be able to answer the test and apply their ability corresponds with the assessment. This research investigate how is the concept of tourism Human Resources Development based on regional Knowledge in The International Bali Tourism Instiute. From the conversion of STPBI Curriculum, it can be seen that in Diploma 3 of Hospitality and Diploma IV of Hospitality Management, able to cover ASEAN/ACCSTP Schematic with method as follows: (1) On The Job Training, (2) Job Introduction Training, (3)Teaching, (4) Programmed Teaching, (5) Training with audio visual aid, (6) vestibule training, (7) Computer-based Training, (8) Job Rotation, (9) Case Study, and (10) Mentoring. With the curriculum and method conformable to ASEAN/ACCSTP Schematic, the students will not encounter any major issue in their assessment since they are well prepared. As the result they will be able to earn their right for their competency certificate and able to compete in this AEC era.Â  Â